CHALLENGES ON IMPLEMENTATION OF INTEGRATED MANAGEMENT OF CHILDHOOD ILNESS (IMCI) - Pinto, Joaquim; Belo, Ostelino da Silva; Leite, Ana do Rosario de Jesus; Ferandes, Manuel da Costa (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2022)
This article in-depth on the critical challenges faced in the implementation of Integrated Management of Childhood Illness (IMCI) as an integrated approach in child health management. The background of the study highlights the complexity of the child health environment, limited infrastructure, and differences in cultural contexts that can affect the effectiveness of IMCI. The research gap is revealed through a lack of in-depth knowledge of all aspects of the challenges faced and a lack of exploration of potential solutions in previous research. This study describes the urgency of research related to the future investment of a nation that is closely related to child health. Presenting past research, this article highlights the knowledge gaps that still need to be filled and the need to optimize child health management strategies. This in-depth approach is considered a novelty of this research, which not only identifies challenges, but also looks for potential solutions to improve the effectiveness of IMCI. The purpose of the study is to identify, analyze, and provide solutions to challenges in IMCI implementation. The benefits of this research include contributing to further understanding of the complexities of IMCI implementation and providing practical guidance and recommendations for the improvement of child health systems. It is hoped that the results of this study can support global efforts in improving children's health through more effective implementation of IMCI.